Developing of a Fuzzy Logic Controller for Air Conditioning System - Mohammed Ali, Issam (Anbar Journal of Engineering Sciences, 2012)
Reducing energy consumption and to ensure thermal comfort are two important considerations in designing an air conditioning system. The control strategy proposed is fuzzy logic controller (FLC).This paper describes the development of an algorithm for air condition control system based on fuzzy logic (FL) to provide the conditions necessary for comfort living inside a building.Simulation of the controlling air conditioning system, on which the strategy is adopted, was carried out based on MATLAB This system consists of two sensors for feedback control: one to monitor temperature and another one to monitor humidity. The controller i.e. FLC was developed to control the compressor motor speed and fan speed in order to maintain the room temperature at or close to the setpoint temperature.